Use of Slow-Release Injectable Moxidectin for Treatment of Dirofilaria immitis Infection During Pregnancy - Alberigi, Bruno; Souza, Celeste da Silva Freitas de; Fernandes, Julio Israel; Merlo, Alexandre; Labarthe, Norma (Frontiers in Veterinary Science, 2020)
Canine heartworm disease is a life-threatening disease caused by Dirofilaria immitis and is prevalent in Brazil. The standard drug for its treatment, melarsomine dihydrochloride, is a fast-killing organic arsenical chemotherapeutic agent not approved in Brazil. Therefore, an alternative strategy, such as macrocyclic lactone in combination with a tetracycline antibiotic, has to be used. The alternative method is a long-term therapy that could lead to compliance issues during treatment. The aim of this case report is to present the efficacy and safety of an off-label biannual administration of slow-release moxidectin, which is formulated for annual administration. This overdose was chosen to test if moxidectin serum levels could be maintained high enough to harm the worms. It was administered to a 4-year-old female dog in combination with doxycycline. The second dose of moxidectin was administered approximately a week before she gave birth to three healthy puppies. Microfilariae were not detected on day 180 of treatment. Serological tests showed that the worms were eliminated, as two negative antigen tests were obtained 6 months apart (at day 180 and day 360 of treatment). Therefore, the off-label biannual use of moxidectin in combination with doxycycline was effective in eliminating D. immitis in 360 days and was harmless for the pregnant dog and her offspring, suggesting that this strategy can be used by practioners in their daily practice.